Economic growth and development - Pandya-Lorch, Rajul (International Food Policy Research Institute, 1994)
Developing countries as a group have experienced rapid economic growth in the last three decades: between 1965 and 1990, their gross national product (GNP) per capita grew at an average annual rate of 2.5 percent to reach US$840 in 1990. However, economic performance has been uneven across developing regions and countries. Poverty is a major consequence of deteriorating or slow economic growth. In 1991, 51.6 percent of the world's population was living in 30 countries that had GNP per capita of less than US$500. World Bank estimates of poverty in the developing world suggest that in 1985, an estimated 1 billion people were poor: they lived below a poverty line of about $420 per person per year. South Asia was home to about half of the developing world's poor, but projections suggest that Sub-Saharan Africa will increasingly become a locus of poverty in coming years as the number of poor people in that region increases from about 184 million in 1985 to 304 million people in 2000. The magnitude of poverty is also anticipated to increase in Latin America and the Caribbean and in the Middle East and North Africa between now and 2000, but to decline by more than half in East Asia from 182 million in 1985 to 73 million in 2000. Overall, the absolute number of poor people in all developing countries is expected to increase slightly, but their share of the total population will decline from 31 percent in 1985 to 24 percent in 2000 due to population growth.